Women and their participation to the local economy - Indriastuti, Indriastuti; Ikmal, Novita Maulida (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
Currently, the percentage of women entrepreneurs in Indonesia is 21%, much better than the global average of 8%. However, there are still many Small and Medium Enterprises (SMEs) managed by women that have not received serious attention from various parties. There is data showing that the management of Small and Medium Enterprises (SMEs) is managed on the basis of kinship and does not yet have strong management, this is what makes women's Small and Medium Enterprises (SMEs) experience ups and downs because in terms of their capital is not yet strong. As time goes by more and more women are also able to succeed in the business world and are able to develop it. This study uses a qualitative approach, with a descriptive method. The results of this study indicate that the participation of women as Small and Medium Enterprises (SMEs) has considerable opportunities and challenges. Nearly 50% of Small and Medium Enterprises (SMEs) at the national and regional levels are women. This is indicated by the number of business units operating in Babat Acne Village, Surabaya City, of 47 business units, 34 of which are managed by women. This means that in this case the patriarchal culture that is rooted in society has begun to disappear.